Application of variable speed drive to overcome air conditioning oversizing issue / Abdul Qayyum Abdul Halim, Tee Boon Tuan and Wan Shah Waliallah Wan Mat Zain - Abdul Halim, Abdul Qayyum; Tuan, Tee Boon; Wan Mat Zain, Wan Shah Waliallah (Universiti Teknologi MARA, 2022)
This paper was aimed at studying the impact of a variable speed drive in tackling the issue caused by an oversized air conditioning system. In this study, oversizing was determined by calculating the actual load demand in an operating air handling unit (AHU), and the formation of mould growth as an indicator of the failure of the AHU to dehumidify the air. A comparison was made between the performance of an actual operating AHU, the performance of the AHU after the installation of a variable speed drive (VSD), and an appropriately sized simulated model of a building using building energy simulation software. The study found that the installed AHU was oversized by 60% and that the installation of VSD is effective in reducing the effective total capacity to meet actual cooling load demand. This study also shows that VSD installation successfully eliminates favourable condition of mould growth by simultaneously reducing AHU capacity and room relative humidity. However, VSD installation should not be standard practice in lieu of proper calculations to determine the appropriate size for an air conditioning system. The simulation result shows that correctly sized air conditioning system will be able to maintain ideal room condition without incurring energy penalties associated with oversizing.